2019
DOI: 10.1017/rdc.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

Direct AMS 14C Analysis of Carbonate

Abstract: We have investigated the possibility of direct accelerator mass spectrometry radiocarbon (AMS 14C) measurement of carbonate samples at ANSTO using the STAR 2 MV tandem accelerator. Each carbonate sample was powdered, mixed with metal powder and pressed into an aluminum cathode for direct carbonate measurement by AMS 14C. Of the three high-purity metal powders (Fe, Nb, and Ag) used in our investigation, Nb was found to be the best metal, which delivered higher carbon beam currents and lower background. Beam cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Direct carbonate 14 C analysis of NAU's C1 blank yields 2.10 ± 0.33 pMC (n = 21) using Fe and 1.49 ± 0.66 pMC (n = 115) using Nb powder. Our direct carbonate blank results are similar to Hua et al (2019) who demonstrated that Nb powder yields lower blanks than either Fe or Ag powders. The source of the direct carbonate 14 C contamination in the NAU blank is unclear but likely stems from a variety of sources including, but not limited to, contamination during processing, carbon contamination in both the metal powders and the C1 powder itself, and uptake from atmospheric sources (Longworth et al 2013).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Direct carbonate 14 C analysis of NAU's C1 blank yields 2.10 ± 0.33 pMC (n = 21) using Fe and 1.49 ± 0.66 pMC (n = 115) using Nb powder. Our direct carbonate blank results are similar to Hua et al (2019) who demonstrated that Nb powder yields lower blanks than either Fe or Ag powders. The source of the direct carbonate 14 C contamination in the NAU blank is unclear but likely stems from a variety of sources including, but not limited to, contamination during processing, carbon contamination in both the metal powders and the C1 powder itself, and uptake from atmospheric sources (Longworth et al 2013).…”
Section: Resultssupporting
confidence: 90%
“…We compiled 60 additional paired determinations generated at UCI or the Australian Nuclear Science and Technology Organisation (ANSTO) from Bush et al (2011), New et al (2019, Parker et al (2019), andHua et al (2019). The respective publications provide the lab procedures and methods used for the additional paired determinations.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations